Written threat: Electrophysiological evidence for an attention bias to affective words in social anxiety disorder. Issue 3 (2nd April 2016) - Wabnitz, Pascal; Martens, Ulla; Neuner, Frank
Abstract : Social anxiety disorder (SAD) is associated with heightened sensitivity to threat cues, typically represented by emotional facial expressions. To examine if this bias can be transferred to a general hypersensitivity or whether it is specific to disorder relevant cues, we investigated electrophysiological correlates of emotional word processing (alpha activity and event-related potentials) in 20 healthy participants and 20 participants with SAD. The experimental task was a silent reading of neutral, positive, physically threatening and socially threatening words (the latter were abusive swear words) while responding to a randomly presented dot. Subsequently, all participants were asked to recall as many words as possible during an unexpected recall test. Participants with SAD showed blunted sensory processing followed by a rapid processing of emotional words during early stages (early posterior negativity – EPN). At later stages, all participants showed enhanced processing of negative (physically and socially threatening) compared to neutral and positive words (N400). Moreover, at later processing stages alpha activity was increased specifically for negative words in participants with SAD but not in healthy controls. Recall of emotional words for all subjects was best for socially threatening words, followed by negative and positive words irrespective of social anxiety. The present findings indicate that SAD is associated with abnormalities in emotional word processing characterised by early hypervigilance to emotional cues followed by cognitive avoidance at later processing stages. Most importantly, the specificity of these attentional biases seems to change as a function of time with a general emotional bias at early and a more specific bias at later processing stages.